2018
DOI: 10.1111/aogs.13433
|View full text |Cite
|
Sign up to set email alerts
|

Preterm premature rupture of membranes: Which criteria contraindicate home care management?

Abstract: Combination of these three criteria is an indication for conventional hospitalization to limit maternal and fetal morbidity. When two criteria are combined, home care should be discussed for each case. If only one unfavorable criteria is present, outpatient management is suitable. To validate these results, a prospective randomized study should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 41 publications
(60 reference statements)
2
21
0
4
Order By: Relevance
“…6 As balancing the risk of chorioamnionitis and neonatal complications related to prematurity is challenging for the physicians, predicting neonatal outcome is one of the key points in the appropriate management of pregnancies complicated by PPROM. 7,8 Although gestational age at delivery is the main determinant of neonatal outcomes, exposure of the fetus to the excessive intrauterine infection/inflammation was another important risk factor for neonatal complications. [9][10][11][12] Thus, estimating maternal and fetal inflammation seems to be reasonable in order to assess the prognosis of the neonate.…”
Section: Introductionmentioning
confidence: 99%
“…6 As balancing the risk of chorioamnionitis and neonatal complications related to prematurity is challenging for the physicians, predicting neonatal outcome is one of the key points in the appropriate management of pregnancies complicated by PPROM. 7,8 Although gestational age at delivery is the main determinant of neonatal outcomes, exposure of the fetus to the excessive intrauterine infection/inflammation was another important risk factor for neonatal complications. [9][10][11][12] Thus, estimating maternal and fetal inflammation seems to be reasonable in order to assess the prognosis of the neonate.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al [9] suggested that HCA confers additional adverse risks for maternal and neonatal, such as earlier gestational age at delivery, neonatal sepsis, hearing impairment, neurologic morbidity, and even death. Petit et al [10] indicated that home care management is a suitable alternative option for PPROM before 35 weeks' gestation when the eligibility criteria are relevant. At present, there are no clear clinical indicators to diagnose the presence of intrauterine infection in PPROM.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that hospital based care should be recommended to women who have all three of these features. 37 Evidence level 2À…”
Section: Evidence Level 2+mentioning
confidence: 99%